Analisis Perubahan Penggunaan Lahan di Kecamatan Argomulyo Kota Salatiga Tahun 2015, 2020, dan 2025 - Dhefani Wahyu Aji Saputra; Aziz Akbar Mukasyaf; Abdul Latif Ashadi; M. Iqbal Taufiqurrahman Sunariya (Mataram University, 2026)
Argomulyo District is a peri-urban area of Salatiga City, Indonesia, experiencing intensive urbanization pressure and designated as an industrial, residential, and sports development zone under Regional Regulation No. 3 of 2023. This study aims to analyze land use change patterns in 2015, 2020, and 2025, and to identify the factors driving these changes. A Random Forest classification algorithm was applied to Sentinel-2 MSI imagery via Google Earth Engine, complemented by in-depth interviews with ten stakeholder informants. Classification accuracy yielded an Overall Accuracy of 97.26% and a Kappa coefficient of 0.9189. During 2015–2025, residential areas expanded by 66.59 ha (31.32%), industrial zones by 5528 ha (23.38%), and agricultural land contracted by 121.87 ha (9.02%), with identical growth rates across both five-year periods indicating structured expansion. Three driving factors were identified: industry-induced demographic pressure generated by a dominant large-scale labor-intensive industrial tenant, progressive industrial investment carrying single-tenant dependency risk, and spatial planning policies that rationalize rather than control ongoing land conversion. Formal permitting compliance proved an inadequate proxy for measuring the effectiveness of land conversion control. These findings indicate that spatial planning instruments in peri-urban areas tend to function as ex-post legitimization of land conversion rather than as effective ex-ante control mechanisms, underscoring the need for spatial-data-driven monitoring frameworks in peri-urban land governance. Strengthening agricultural land protection through legal establishment of a Sustainable Food Agricultural Zone, stricter spatial detail plan instruments, and periodic remote sensing-based monitoring is recommended.